Consulting report - Euromotors S.A - Saire Donayre, Juan Diego (2017)
Euromotors S.A. is the exclusive brand representative of the Volkswagen, Audi, Porsche, and SEAT brands among others within 11 strategic business units in Peru. Since its foundation, the firm has since grown exceptionally in size, scope and sophistication from their original operational function as an automobile importer to their current status engaged in the sale of vehicles, new and used cars, servicing and sale of original spare parts. As a multi-brand firm, it maintains 1,052 employees who function relatively autonomously within each business division for the separate brands. In order to propel the firm forward as a cohesive unit, synergies within need to be created to eliminate the replication of processes and procedures and to ultimately streamline overall organizational function. After a few years of declining profitability, Euromotors is looking at opportunities to improve its competitive position within the Peruvian automotive retail sector, which is rapidly changing and increasingly competitive market. In order to withhold a competitive advantage, a micro-pilot project has been designed within the consulting process, which has taken deep rooted analysis at both the internal and external environmental factors, to be implemented with Euroshop, Euromotors’ most profitable division. A cultural transformation will impact the sales force team of Euroshop; however, before it can be properly administered, overcoming organizational resistance to change must be dealt with. The proposed solution develops method for Euromotors to incrementally overcome the resistance to change in a multi-step system, to increase employee motivation and unity while increasing intrinsic responsibility to function as a team throughout the entire firm. This proposal considers the necessity of maintaining commitment to the strategic goals of the company. Through the development of a strategic map and a KPI based scorecard, the firm will have visibility on the key factors in garnering true change. Project timeframe is estimated in six months and total budget in USD 25,500